PTU-089 Follow-up of patients with primary sclerosing cholangitis – do we meet international standards?. (17th June 2017) - Lin, S; Smith, N; Valliani, T; Lockett, M
Abstract : Introduction: Primary Sclerosing Cholangitis (PSC) is a chronic progressive cholestatic liver disease associated with significant complications such as cirrhosis, fat-soluble vitamin deficiency, metabolic bone disease, cholangiocarcinoma and colorectal carcinoma (CRC). We reviewed our current practice against the American Clinical Gastroenterology (ACG) guidelines on PSC, with the aim of developing trust guidelines to standardise follow-up in both hepatology and Inflammatory Bowel Disease (IBD) clinics. Method: 42 patients with a diagnosis of PSC were identified on retrospective review of clinic letters between 2012–2016. Demographic data, presence of IBD, investigations at diagnosis and investigations at follow-up were collected by interrogating clinic letters, pathology results and endoscopy reports. Results: 37 patients were seen in a mixed hepatology and gastroenterology clinic, 5 in IBD clinics. 5 patients died during follow-up, 2 from causes directly related to PSC. Of the remaining 37 patients, 60% were male, median age 61 (23 – 91). 84% of patients were diagnosed prior to 2015 when this guideline was published. 80% of patients had concurrent IBD, pan-colitis ulcerative colitis (UC) being predominant. 5 patients had undergone a liver transplant. Of the recommended tests at diagnosis, 56% of patients without IBD had screening colonoscopy, 32% had IgG4 levels measured and 27% underwent a Fibroscan. Investigations undertaken at follow-up are shown in Table 1. Only 2 patients failed to have annual colonoscopy, 1 due to appointment delay and the other declined surveillance. Comparing surveillance standards, 75% of patients in IBD clinics had chromoendoscopy versus 43% in hepatology clinics. Poor bowel prep and a lack of request were noted as reasons for this. Similarly, 50% of hepatology clinic patients had regular biliary imaging, compared to 25% in IBD clinics. Conclusion: PSC patients require multiple investigations at diagnosis and follow-up, some of which may have an important impact on the risk of malignancy. This study demonstrates a need to improve and standardise management in both hepatology and IBD clinics in this group of patients. At present, there are no established UK guidelines, although we have since developed trust guidelines and changes implemented in the form of PSC patient proformas and investigation "order-sets" to improve the care of patients with PSC, which will be re-audited. Disclosure of Interest: None Declared